Attitudes and Behaviors of Mobile Network Operator Customers Contributions toward empirically founded marketing strategies for mobile navigation and Internet services - Gerpott, Torsten J. 1958-2023 (Rainer Hampp Verlag, 2010)
The market for mobile voice communication approaches its saturation level in many industrialized nations. Prices for mobile voice telephony have been and still are under pressure. Against this background, mobile network operators (MNO) are searching for new services which may bring them back to previous revenue growth trajectories. Among these potential innovations are mobile Internet (MI) services in general and mobile network-based navigation services (MNS) in particular. Unfortunately, to date, these kinds of offerings have not been adopted as fast and are not used as extensively as expected by MNO in Germany, but also in other countries around the world. During the past few years, these subscription and usage gaps have triggered quite a number of practitioner publications and scholarly contributions on critical factors explaining consumers' initial MI or MNS adoption decisions and subsequent use behaviors. Regrettably, much of this writing is purely speculative and does not incorporate empirical data on attitudes and behaviors of MNO customers in Germany in the context of customer acceptance of MI and MNS offerings. In light of this gap the present book contains an assortment of five empirical papers on MI and MNS acceptance drivers among German-speaking mobile communication consumers. The articles are of interest to both practitioners involved in the development of marketing strategies for MI and MNS as well as business and consumer psychology scholars who are concerned with better understanding the demand for innovative mobile service offerings from a residential customer's perspective